2010
DOI: 10.1007/s00204-010-0620-y
|View full text |Cite
|
Sign up to set email alerts
|

An in vivo assessment of the genotoxic potential of bisphenol A and 4-tert-octylphenol in rats

Abstract: Bisphenol A (BPA) and octylphenol (OP) are industrial chemicals used in the manufacture of polycarbonate plastics, epoxy resins, and non-ionic surfactants. In the present study, we investigated the possible in vivo genotoxic effects of these compounds in rats using single-cell gel electrophoresis, the so-called comet assay. Adult male Wistar albino rats were divided randomly into six groups as follows: BPA125 (received 125 mg/kg bw BPA; n = 6), OP125 (received 125 mg/kg bw OP; n = 6), BPA250 (received 250 mg/k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 51 publications
2
22
0
1
Order By: Relevance
“…36 These results suggest that exposure to a low dose of BPA may lead to the persistence of mDSBs by inhibiting their repair, although high doses of BPA have been reported to be genotoxic. 37 Subsequently, these unresolved mDSBs in pachytene spermatocytes result in the disruption of meiotic progression and chromosome abnormalities, such as asynapsis, chromosomal aberrations, and interrupted regions of SYCP3 staining, as also demonstrated by previous studies. 9, 14 …”
Section: Discussionsupporting
confidence: 59%
“…36 These results suggest that exposure to a low dose of BPA may lead to the persistence of mDSBs by inhibiting their repair, although high doses of BPA have been reported to be genotoxic. 37 Subsequently, these unresolved mDSBs in pachytene spermatocytes result in the disruption of meiotic progression and chromosome abnormalities, such as asynapsis, chromosomal aberrations, and interrupted regions of SYCP3 staining, as also demonstrated by previous studies. 9, 14 …”
Section: Discussionsupporting
confidence: 59%
“…Furthermore, Tyl et al ( 2002 ) investigated physiological parameters, but did not assess biochemical changes. Other authors have studied BPA and have reported that it caused various effects, including genotoxicity and clastogenicity in blood cells (Ulutaş et al 2010 ;Dobrzyńska and Radzikowska 2013 ;Tiwari et al 2012 ), increased susceptibility to chemically induced mammary carcinogenesis (Jenkins et al 2012 ), and induced meiotic aneuploidy in oocytes (Hunt et al 2003 ), suggesting possible modifi cation of the DNA in male germ cells that may be transmitted to the next generation (Salian et al 2011 ).…”
Section: Effects Of Bisphenol a On Spermatogenesismentioning
confidence: 99%
“…The worldwide distribution of BPA in various environments was considered as the sources of BPA exposure to human beings (Kang et al 2006b;Ulutao et al 2011). Another way of exposure to BPA occurred through ingestion followed by accumulation in the fatty tissues (Oehlmann et al 2008;Sanchez-Avila et al 2009).…”
Section: Introductionmentioning
confidence: 99%